2019
DOI: 10.3389/fchem.2019.00252
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dots Synthesis Through Direct Laser Patterning: A Review

Abstract: In this brief review the advances on Direct Laser Patterning (DLP) for the synthesis of photo-luminescent semiconductor quantum dots (QDs) belonging to II-VI groups, especially in solid state using laser-assisted conversion are reported and commented. The chemistry of the precursor synthesis is illustrated because it is a crucial step for the development of the direct laser patterning of QDs. In particular, the analysis of cadmium (bis)thiolate and cadmium xanthates precursors after thermal and laser treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 86 publications
0
29
0
Order By: Relevance
“…The practical use of direct laser writing strongly relies on its power threshold. In most cases, direct laser writing using a low power laser is much preferred . We then investigated the influence of precursor concentration on the threshold laser power by monitoring the PL intensity with increasing laser power.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The practical use of direct laser writing strongly relies on its power threshold. In most cases, direct laser writing using a low power laser is much preferred . We then investigated the influence of precursor concentration on the threshold laser power by monitoring the PL intensity with increasing laser power.…”
Section: Resultsmentioning
confidence: 99%
“…In most cases, direct laser writing using a low power laser is much preferred. 43 We then investigated the influence of precursor concentration on the threshold laser power by monitoring the PL intensity with increasing laser power. As shown in Figure S6, it is found that the PL intensity of the resulting patterned γ-CsPbI 3 PQDs first increased and then decreased with the laser irradiation power increasing from 1.36 to 3.00 mW.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…22,24,29 Alternatively, nanoparticles can be synthesized directly in a preformed polymer matrix by decomposing suitable precursors under thermal treatment 30 or light irradiation. 31,32 Formation of both the nanocrystals and polymer matrix can occur at the same time. 22 Nevertheless, irrespective of the preparation method of polymer composites with embedded QDs, there are two critical issues which should be solved.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of the cadmium-chalcogenide QDs when activated by an external source of energy in the form of heat or radiation is of particular interest, because it can be localized allowing the patterning of the semiconductor QDs. Recently this basic idea has been shown possible by several authors and it is the basis of the direct laser patterning approach, i.e., the process in which the laser source modifies a material to obtain the desired effect (QDs formation) [17] only in specific area of the sample (patterning) [18,19]. To date, the work showed in these papers is focused mainly on the formation of CdS QDs from the cadmium bis(benzythiolate) precursor [20] and only recently of the CdSe QDs from cadmium 2-(N,N-dimethylamino)ethylselenolate [21,22].…”
Section: Introductionmentioning
confidence: 99%